Una storia di Tempo Reale: carte e memorie intorno a un'esperienza fiorentina di ricerca musicale (1987-2022) - Sarno, Giulia (Roma Squilibri, 2023)
Founded in 1987 by Luciano Berio, Tempo Reale has formed an important hub for research, production, teaching and development in the fractious field of electronic music. Set initially on the possibilities offered to the world of music by new digital technologies, the Institute has since assisted numerous composers, from Battistelli to Sciarrino, Stroppa to Guarnieri, in the creation of new works marked by the use of electronics and has acted as an incubator for numerous other projects related to technologies applied to sound, fostering the emergence of many young musicians. Through systematic reconnaissance in archival documents and also drawing on the living voices of witnesses and protagonists, the volume traces the history of these thirty-five years in which Tempo Reale has gained a prominent position in the international context of electronic music whose events are likewise recalled in the volume to highlight the novelty represented by this Florentine experience of musical research. (translated by Deepl.com)
Includes bibliographical references (pages 353-383) and index.
Keywords: Berio, Luciano -- 1925-2003; Tempo reale; Electronic music; Music history; Teaching; Composing; Artistic research; Florence (Italy)